FAKTOR KELELAHAN KERJA PADA DRILLING RIG OPERATOR SERVICE DI PT. X MINAS PEKANBARU - Venesya , Yolanda; Edigan , Firman; Gumayesty, Yeyen; Priwahyuni, Yuyun (Journal of Hospital Administration and Management (JHAM), 2025)
Work fatigue is a feeling that arises in a situation that generally occurs in workers, where workers are no longer able to do work. Fatigue in workers found at PT. X, namely 5 workers experiencing complaints of fatigue at work including complaints about increasing age accompanied by decreasing physical strength, also the duration of work that exceeds the applicable provisions, nutritional status, work shifts, and workload. The purpose of this study was to determine the factors associated with work fatigue in Drilling Rig Operator Service This type of research is quantitative analytic with a cross-sectional design. The population in this study were 153 respondents with a sample of 60 respondents. Sampling using probability technique with simple random sampling method. The analysis used univariate and bivariate analysis using the chi-square test. The results obtained, there is a relationship between age and fatigue, namely (p-value=0.001, POR=18.400), then there is a relationship between nutritional status (p-value=0.001, POR=16.762), there is a relationship with work duration (p-value=0.038, POR=5.938), there is a relationship with work shifts (p-value=0.0001, POR=16.714) and there is a relationship with workload (p-value=0.009, POR=6.067). It can be concluded that there is a relationship between age, nutritional status, work duration, work shifts and workload with fatigue. PT. X should reduce fatigue in workers by giving time off, appreciation or rewards to workers to improve the quality of work. And hold a family gathering once a month. Keywords : fatigue , nutritional status, work duration, work shifts and workload